Pencegahan Fraud Pengadaan Barang Dan Jasa Melalui Whistleblowing System Dan Kesadaran Anti-Fraud - Siti Destiah Fitriani; Evada Dewata; Desi Indriasari (LPPM ISNJ Bengkalis, 2022)
This study aimed to see the effect of the whistleblowing system and anti-fraud awareness on fraud prevention. This research is quantitative research that uses primary data as its data source. The method used in this study was a survey method by distributing questionnaires to 87 respondents who were members of the goods and services procurement committee at the regional apparatus organization (RAO) of Palembang city. Data were analyzed using multiple linear regression with the SPSS 25 tool. The results showed that the whistleblowing system and anti-fraud awareness partially and simultaneously positively and significantly affect preventing fraud in procuring goods and services. The research has implications for RAO Palembang city to improve the implementation of the whistleblowing system. Providing a suggestion box in each RAO Palembang city office so that every party in the organization can report if they see fraud, especially in procuring goods and services. Then the Palembang city RAO can also provide training to all employees to raise awareness and knowledge about the dangers of fraudulent procurement of goods and services.